Estratégia de seleção para resistência a mancha angular no melhoramento do feijoeiro - Silva, Alice Pereira (2019)
A recurrent selection program (RS) aiming at resistance to angular leaf spot in common bean, which is caused by P. griseola fungus, has been conducted in Minas Gerais state since 1998. In this program, the selection of progenies for recombination is performed in the field, under conditions of natural occurrence of the disease. However, in some years and/or places other diseases occur that make difficult the identification and selection of resistant progenies, and may interfere in the success of the program. An alternative would be to use artificial inoculation with pathogen isolates under controlled conditions. Although, the question is whether the progenies selected with artificial inoculation would also be resistant under field conditions at different sites and years, since the variability of the pathogen is great. In order to respond to this questioning, 119 progenies from this RS program were evaluated, of which 60 were obtained by selection under conditions of natural occurrence of the disease in the field and 59 obtained byselection under controlled conditions. These progenies were evaluated for the severity of the disease, in the S0:3 and S0:4 generations, in the "dry" season of 2017 and 2018, respectively, under natural conditions in Lavras and Lambari, MG. Using a mixture of pathogen isolates collected in these experiments, the same progenies were also evaluated with artificial inoculation under controlled conditions. Individual and joint analyses of variance were performed and estimated genetic and phenotypic parameters. Coincidences in progenies selection were also obtained for resistance or susceptibility in the two evaluation conditions. It was verified that the evaluation of angular leaf spot severity in the common bean with artificial inoculation under controlled conditions can lead to the selection of progenies that will be susceptible under natural conditions of disease occurrence. This evaluation should be used for initial screening and elimination of the most susceptible progenies. The selected ones should be submitted to the field evaluations, in several environments, with natural incidence of the pathogen, to identify those with broader resistance.